(untitled) (Research, Society and Development, 2021)
Aimed to evaluate the sanitary conditions of establishments sellers of fresh beef from Castanhal microregion - Pará, as well as determine the microbial load of meat sold in the cities of the microregion. For this, hygienic - sanitary evaluation was held in 68 establishments of the cities of Bujarú, Castanhal, Inhangapí, Santa Izabel do Pará and Santo Antônio do Tauá through completion of check list made in accordance with Brazilian law. Analysis of positive Staphyloccoccus coagulase, 35°C and 45°C coliforms, and Salmonella spp. were performed in 63 samples collected in the establishments visited. The results of our study show that 88.8% of establishments had unsatisfactory hygienic condition, 6.4% of sites were considered fair and only 4.8% were considered satisfactory. The presence of Salmonella spp. was detected in only one sample collected in Santo Antônio do Tauá city and one sample collected in Inhangapi city. Meat samples analyzed 92% and 73% coliforms at 35°C and 45°C, greater than 1100 MPN/g, respectively, and positive Estaphylococcus coagulases counts ranged from <1.0 x 101 and 8.4 x 102 CFU/g. Under Brazilian law, is recommended only for Salmonella spp. being deemed unfit for human consumption, even when evidence of high levels of indicator microorganisms and failures in hygienic - sanitary commercial establishments. We conclude that establishments that sell beef "natural" condition of Castanhal microregion showed unsatisfactory sanitary conditions, confirmed by high counts of indicator microorganisms found in the samples studied.